PRODUCTIVITY OF SUMMER LEGUME FORAGES INTERCROPPED WITH MAIZE AS AFFECTED BY MIXED CROPPING IN DIFFERENT SOWING TECHNIQUES - A. Iqbal; N. Akbar; H. Z. Khan; R. N. Abbas; J. Ahmad (Journal of Animal and Plant Sciences, 2012)
This study was conducted during 2003 and 2004 to study the influence of mixed cropping on forage yield and quality. Three summer forage legumes viz. clusterbean, cowpea and ricebean were intercropped with maize in different sowing techniques such as broadcast with blended seed of maize and legume, line sowing with blended seed of maize and legume and line sowing in alternate rows of maize and legume. The experiment was laid out in randomized complete block design with four replications.  Highest green forage yield of 13.31 t ha-1 was obtained from cowpea intercropped with maize in 30 cm spaced lines in alternate rows. This treatment combination also increased the leaf area index of 1.88 and 2.49 during the first and second year of study, respectively leading to improvement in nutritive value as evidenced by its protein contents, compared to other legume intercrop combinations. In conclusion, to get better yield of quality fodder, forage maize should be intercropped with forage legumes, preferably cowpea, under the planting pattern of 30 cm spaced lines in alternate rows.
Keywords: Clusterbean; cowpea; ricebean; intercropping; planting pattern; forage maize